Penerapan Model Nature of Science untuk Meningkatkan Pemahaman Konsep pada Pembelajaran IPA - Intan Cahyaningrum; Ulfatun Nikmah; Harum Isni Wiharti; Meylina Arisnaini; Sri Suciatun; Kusmiyati, Nurul (Kampus Akademik Publiser, 2025)
Conceptual understanding is a fundamental aspect of meaningful learning. Without a solid grasp of concepts, students tend to merely memorize information without being able to apply it in real-life situations. One instructional model that can foster this ability is the Nature of Science (NOS) learning model. The purpose of this study is to describe the steps, advantages, and disadvantages of implementing the Nature of Science learning model in science education at Madrasah Aliyah Negeri 2 Rembang and Madrasah Aliyah Negeri Sukoharjo. This research employed a qualitative approach. The subjects of the study were science teachers at Madrasah Aliyah Negeri 2 Rembang and Madrasah Aliyah Negeri Sukoharjo. Data were collected through interviews, observations, and documentation. The results of the study are as follows: (1) The steps of the Nature of Science model include background readings, case study discussions, inquiry lessons, inquiry labs, and historical studies; (2) The advantages of the model include increasing student activeness and self-confidence, providing enjoyable and contextually relevant learning experiences, promoting the development of scientific process skills, and helping students gain hands-on experience through practical activities that allow them to discover concepts independently; (3) The disadvantages of the Nature of Science model are that it is more suitable for science and technology fields, requires high levels of precision, perseverance, and diligence, and that experimental outcomes may not always align with expectations due to factors beyond students’ control or experience. The conclusion of this study is that the Nature of Science learning model can be applied in the teaching process as an effort to enhance students' conceptual understanding at the Madrasah level.